Analysis of the Double Defendant System of Administrative Reconsideration - Li, Yidi; Li, Xintong (International Journal of Social Sciences and Public Administration, 2024)
Since 2014 Administrative Procedure Law revised and established the administrative reconsideration Double Defendant System, the reconsideration “Maintenance meeting” phenomenon although has changed, but all kinds of problems come one after another, such as confusion of function orientation, violation of the principle of “Evidence before judgment”, increasing the burden of litigation and impairing the plaintiff’s right of free choice. Article 10 of the Administrative Review Law of the People’s Republic of China (revised)(draft for consultation) , published by the Ministry of Justice on November 24,2020, even abolished thedouble defendant System, although it was reinstated in the new law on Administrative Review adopted at the fifth session of the Standing Committee of the National People’s Congress on September 1,2023, but this kind of system’s repetition reflects undoubtedly double defendant System has not developed mature, needs to continue consummates.